Effect of an educational intervention based on the model of health beliefs in self-medication of Iranian mothers - Kouhpayeh, Amin; Jeihooni, Ali Khani; Kashfi, Seyyd Hannan; Bahmandoost, Mina (Investigación y Educación en Enfermería, 2017)
Objective. This study sought to determine the effect of education based on the model of health beliefs in self-medication of women in Iran. Methods. Quasi-experimental study in a group of mothers (N = 90, 45 in the intervention group and 45 in the control group) users of health centers from the city of Fasa, province of Fars, southern Iran. Before and after the educational intervention (four training sessions in three months), a questionnaire was applied containing questions based on the model of health beliefs, on the components of knowledge, vulnerability, severity, benefits, and barriers perceived, and practices on self-medication. Results. Prior to the educational intervention, the level of knowledge, sensitivity, intensity, and benefits of self-medication were equal in both groups; however, after the educational intervention, it was observed that the intervention group improved in all components of evaluation and diminished barriers perceived and self-treatment practices. Conclusion. The educational intervention based on the model of health beliefs was effective in reducing self-medication practices in the group of mothers. Hence, this type of training is recommended in health centers to diminish the frequency of this practice. How to cite this article: Kouhpayeh A, Jeihooni AK, Kashfi SH, Bahmandoost M. Effect of an Educational Intervention Based on the Model of Health Beliefs in Self-Medication of Iranian Mothers. Invest. Educ. Enferm. 2017;35(1):